(untitled) (Journal of Advanced Research in Social Sciences, 2022)
Tourism has traditionally been considered an activity contributing to human quality of life and well-being. Under the current situation of the COVID-19 pandemic, tourism has been severely affected. However, it is important to look ahead and consider the factors to help revitalize tourism. This study focuses on the need for co-creative actions in tourism, using the characteristics of expression in social media during the COVID-19 infection in Japan. The key factor of this research is the service-dominant logic (SDL). SDL signifies the exchange of services, and is based on the concept that value is created only when one entity provides services and another entity receives them. Upon applying SDL to the field of tourism, it was found that the main entity providing services is the “tourism industry” and “residents,” while the entity receiving services is the “customer/consumer” as a “tourist.” In SDL, co-creative activities are attracting attention, because both the provider and the recipient can create values as a service. As the COVID-19 pandemic enters from subsidence to expanding periods, this study analyzes how tourism-related emotional expressions transitioned, and the feelings of resilience, based on social media. This research obtained the following three features. First, co-creative activities were perceived as more positive activities during the pandemic. Second, service-related emotional expressions continued to be expressed during the pandemic. Thirdly, expressions with a temporal perspective representing the future were used.